Comparative clinical outcomes evaluation of hospitalized patients infected with Clostridioides difficile ribotype 106 vs. other toxigenic strains. (December 2021) - Almutairi, Masaad Saeed; Gonzales-Luna, Anne J.; Alnezary, Faris S.; Fallatah, Saad B.; Alam, M.Jahangir; Begum, Khurshida; Garey, Kevin W.
Abstract: Background: Although Clostridioides difficile surveillance often identifies emerging strains, clinical outcome evaluations are rarely performed. Ribotype (RT) 106 is a commonly isolated C. difficile strain worldwide; however, studies investigating RT 106 clinical outcomes are limited. The purpose of this study was to investigate clinical outcomes of RT 106 infections compared with two other endemic strains of varying virulence. Methods: This multicenter study evaluated adults hospitalized with C. difficile infection (CDI). C. difficile samples underwent PCR ribotyping and patients infected with RT 106 were compared to patients infected with a known hypervirulent strain (RT 027) and a strain associated with less virulence (RT 014–020). Electronic medical records were reviewed by blinded investigators to assess the primary outcome of poor clinical outcome (composite of initial clinical failure, discharge to a higher level of care, 90-day CDI recurrence, and CDI-contributable mortality). Results: A total of 396 patients with CDI were identified (RT 106, 32.3%; RT 027, 29.3%; RT 014–020, 38.3%). Patients infected with RT 014–020 less often experienced a poor clinical outcome (40%) compared with RT 106 (56%) and RT 027 (65%) infection (P < 0.0001). After controlling for covariates and using RT 014–020 as a comparator, patients infected with RT 106 (OR, 2.25; 95% CI, 1.36–3.73) or RT 027 (OR, 2.56; 95% CI, 1.52–4.31) had higher odds of poor clinical outcome. Using RT 027 as the comparator, only RT 014–020 was associated with lower odds of poor clinical outcome (OR, 0.42; 95% CI, 0.27–0.65). Conclusion: This study demonstrated that the emergent C. difficile RT 106 was associated with increased rates of poor clinical outcomes compared to RT 014–020 and comparable poor clinical outcomes to RT 027. These findings can help to better understand the clinical significance of this and future emerging ribotypes.